2016
DOI: 10.1121/1.4947540
|View full text |Cite|
|
Sign up to set email alerts
|

Asymptotic limits of some models for sound propagation in porous media and the assignment of the pore characteristic lengths

Abstract: Modeling of sound propagation in porous media requires the knowledge of several intrinsic material parameters, some of which are difficult or impossible to measure directly, particularly in the case of a porous medium which is composed of pores with a wide range of scales and random interconnections. Four particular parameters which are rarely measured non-acoustically, but used extensively in a number of acoustical models, are the viscous and thermal characteristic lengths, thermal permeability, and Pride par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…in the above equation is the Pride parameter 9 discussed later at the end of this section making reference to the work by Horoshenkov et al 20 The above expression suggests that the flow resistivity can be determined from the asymptotic behaviour of the imaginary part of the dynamic density by estimating the low-frequency limit (ω ω v ) of Figure 3 shows the behaviour of Eq. (7) plotted as a function of frequency for reticulated foam (see Fig.…”
Section: Reticulated Foams and Fibrous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the above equation is the Pride parameter 9 discussed later at the end of this section making reference to the work by Horoshenkov et al 20 The above expression suggests that the flow resistivity can be determined from the asymptotic behaviour of the imaginary part of the dynamic density by estimating the low-frequency limit (ω ω v ) of Figure 3 shows the behaviour of Eq. (7) plotted as a function of frequency for reticulated foam (see Fig.…”
Section: Reticulated Foams and Fibrous Materialsmentioning
confidence: 99%
“…In ref. 20 it was shown that in the case of a porous medium with cylindrical pores which radius is log-normally disctributed; the Pride parameter is equivalent to β = 4/3e…”
Section: Granular Materialsmentioning
confidence: 99%
“…The acoustical properties of a system of parallel identical non-uniform pores composed from n adjoining cylinders with a distribution of areas An but equal section lengths ( ) have been considered [20], but the expression given for complex density, viz.…”
Section: Periodically Non-uniform Slitsmentioning
confidence: 99%
“…Again, using the effective medium approximation, the overall impedance is calculated from the impedance of hard-backed porous layer section of thickness d (from equation 7in parallel with that of the unit cell shown in Fig. 6(b) (from equations (19) and (20)).…”
Section: Partitions With Gapsmentioning
confidence: 99%
“…Calculating the acoustic impedance of the ground, , can be done be various methods, however assuming the ground to be porous, the method proposed by Horoshenkov et al is used [4] in this paper. This model makes use of the median pore size which relates to the ground impedance.…”
Section: Acoustic Foundationsmentioning
confidence: 99%